2013
DOI: 10.1590/s0034-737x2013000100018
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento do maracujá doce em Viçosa, Minas Gerais

Abstract: Fruit development of sweet passion fruit in Viçosa, Minas GeraisThe physical, chemical and physiological changes during the development of sweet passion fruit, from anthesis to ripening in the plant, were evaluated. Fruits had a slightly oblong shape, a simple sigmoidal pattern of development and climacteric pattern for respiration. Fruit development was divided into three phases: cell division up to 4.70 days after anthesis (daa); cell expansion from 4.70 daa to 28.94 daa and maturation from 28.94 to 91 daa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
5
0
2
Order By: Relevance
“…, close to those found byJung et al (2007a, b), in 36 crosses of P. alata, which was 30.26%;Alves et al (2012a) in mature fruits of P. alata after 30.6 days of anthesis, the proportion of 74.10% of pericarp (peel), 24.46% of pulp and 3.14% of seeds, while in P. edulis f. flavicarpa, Negreiros et al (2008) observed pulp yield between 27.65 and 45.83%. Like the physical characteristics, the chemicals are very important in a series of factors such as the conservation of the pulp and the amount of sugars to be added to the juice.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…, close to those found byJung et al (2007a, b), in 36 crosses of P. alata, which was 30.26%;Alves et al (2012a) in mature fruits of P. alata after 30.6 days of anthesis, the proportion of 74.10% of pericarp (peel), 24.46% of pulp and 3.14% of seeds, while in P. edulis f. flavicarpa, Negreiros et al (2008) observed pulp yield between 27.65 and 45.83%. Like the physical characteristics, the chemicals are very important in a series of factors such as the conservation of the pulp and the amount of sugars to be added to the juice.…”
supporting
confidence: 91%
“…The total acidity of fruits of genotypes 2, 4, 7, 8, 11-13, 17-22, 25, 27 and 31 stands out in the cluster of higher means, with values ranging from 5.71 to 7.48% (Table 2). Freitas et al (2006) working with the same species found 1.70 g of citric acid / 100 mL, and according to Alves et al (2012a) For both the industry and the fruit market in natura, the soluble solids (SS) content must be high, and the higher the SS content the lower the quantity of fruits required for the juice concentration (Negreiros et al, 2008). The genotypes 15; 17; 22 and 24 presented the lowest levels of SS,17,20;17.77;17.85 and 16.15 °Brix,respectively, whose values are below the mean that was 19.67 ° Brix (Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…We also determined the minimum critical point (PC min ), which represents the moment in the accumulation curve in which expressive gains in dry matter start to occur, and the maximum critical point (PC max ), which represents the moment when the accumulation of the components begins to stabilize, as previously described (Alves et al, 2013):…”
Section: Methodsmentioning
confidence: 99%
“…Populations with one and six plants per pit did not differ in the titratable acidity of fruits between harvests, but reductions were occurred from the first to the second harvest in the arrangements with two, 4.5 to 3.3% citric acid (-27%), and three plants, from 3.7 to 3.1% citric acid (-16%) ( Table 2). The citrus acid is rapidly accumulated after the physiological maturity of the fruit and it is degraded during ripening (Vianna-Silva et al, 2010;Botelho et al, 2019) to meet the respiratory demand of this climacteric fruit (Alves et al, 2013 ). According to Cavichioli et al (2008) and Vianna-Silva et al (2008 temperature is a preponderant factor in the concentration of citric acid.…”
Section: Ttitratable Total Aciditymentioning
confidence: 99%
“…On average it was 1.4 °Brix more in cultures with one and three plants per pit ( Table 2). The soluble solids increase during the growth/maturation of passion fruit (Coelho et al, 2010;Vianna-Silva et al, 2010;Alves et al, 2013), and it is also one of the most influenced physical-chemical atributes by the harvest season. The highest (16.5 °Brix) and lowest (12.6 °Brix) soluble solids values were in the fruits of the second crop in the arrangement with one plant and in the first crop of the crop with six plants per pit, respectively.…”
Section: Soluble Solidsmentioning
confidence: 99%